ChemInform Abstract: Synthesis, Structure, and Biological Applications of α‐Fluorinated β‐Amino Acids and Derivatives. Issue 12 (14th March 2013) - March, Taryn L.; Johnston, Martin R.; Duggan, Peter J.; Gardiner, James
Abstract Review: 133 refs.